Prevalence and Predictors of Sepsis Death in Patients With Chronic Heart Failure and Reduced Left Ventricular Ejection Fraction. Issue 20 (16th October 2018) - Walker, Andrew M. N.; Drozd, Michael; Hall, Marlous; Patel, Peysh A.; Paton, Maria; Lowry, Judith; Gierula, John; Byrom, Rowenna; Kearney, Lorraine; Sapsford, Robert J.; Witte, Klaus K.; Kearney, Mark T.; et al.
Abstract : Background: Noncardiovascular death is increasingly common in people with chronic heart failure (CHF), yet its causes remain poorly characterized. We aimed to define the prevalence of sepsis death in people with CHF and to ascertain its risk marker profile. Methods and Results: We conducted a prospective cohort study of 1802 patients with CHF and left ventricular ejection fraction ≤45% attending CHF clinics in 4 United Kingdom hospitals between 2006 and 2014. Mode of death was defined over a 10.3‐year follow‐up period (mean 4 years). Competing risk regression defined mode‐specific hazard ratios for sepsis, other noncardiovascular, progressive heart failure, and sudden cardiac death in relation to established heart failure prognostic markers. Of 737 deaths, 173 (23.5%) were due to sepsis; respiratory tract infections accounted for 69.9% (n=121) of these events. Those who died from sepsis were older, had higher platelet counts, and had a higher prevalence of chronic obstructive pulmonary disease than those who died from other causes. Sepsis death was independently associated with older age (hazard ratio=1.05; 95% confidence interval 1.03‐1.07), greater prevalence of chronic obstructive pulmonary disease (2.43; 1.74‐3.40), male sex (1.73; 1.16‐2.60), lower log serum vitamin D (0.68; 0.49‐0.95), and higher platelet count (1.002; 1.000‐1.005) than nonsepsis death. Established heart failure prognostic markers exhibited different patterns of association with sepsis death, other noncardiovascular death, progressive heart failure death, and sudden cardiac death. Conclusions: Sepsis is a major contributor to death in people with CHF and has a different risk marker profile from other modes of death, suggesting that it may be amenable to targeted preventative strategies.